Outcome Analysis of Project-Based Training on Book Chapter Writing for Elementary School Teachers - Theresia Wariani; Alfons Bunga Naen; Vinsensia H. B. Hayon; Hironimus Tangi; Yanti Rosinda Tinenti; Ilidio Ximenes Moreira (Postgraduate, University of Mataram, 2026)
This study aims to evaluate the effectiveness of a training project using the Project-Based Learning (PPjBL) model in enhancing elementary school teachers’ competencies in writing and documenting best practices into book chapters. This study employs a mixed-methods approach with a pre-experimental design (one-group pretest–posttest design). The study participants consisted of 9 elementary school teachers selected using saturation sampling. Quantitative data were obtained through pretest and posttest assessments of writing skills, while qualitative data were collected through observations of the implementation of the PPjBL model and perception questionnaires. The results showed a significant improvement in teachers’ writing skills after the training (p < 0.01), particularly in the aspects of content, structure, and academic language. The implementation of the PPjBL model fell into the “mostly implemented” category with an average score of 3.25, indicating that the model’s stages were carried out fairly optimally. In addition, teachers’ perceptions of the PPjBL model fell into the “very positive” category, with an average score of 3.54, particularly regarding the aspects of relevance and the ability to produce tangible outputs in the form of books. These findings indicate that PPjBL is effective and relevant as a project-based training model focused on publication-oriented outputs. This study contributes to the development of a professional teacher training model that not only enhances competencies but also produces tangible outcomes that can be utilized within the educational community.